DESIGNING CORAL REEF TRANSPLANTATION PROGRAM WITH LOCAL COMMUNITY IN FORM OF MARINE ECOTOURISM TOUR PACKAGE - Wirakusuma, Reiza Miftah; Sukirman, Oman; Waliyudin, Ridwan Taufik; Putra, Rifki Rahmanda (Journal of Indonesian Tourism, Hospitality and Recreation, 2019)
ABSTRAKSejak 1990 Pangandaran telah berkembang menjadi salah satu tujuan wisata utama di Jawa Barat yang memfokuskan pengembangannya pada wisata bahari. Perkembangan itu menarik banyak wisatawan dan berdampak pada kondisi ekosistem laut. Terumbu karang secara perlahan dirusak oleh kegiatan wisatawan, limbah plastik dan polusi, sehingga kejernihan air terdegradasi. Program ini dilakukan untuk menganalisis tingkat kerusakan terumbu karang dan kesiapan masyarakat dalam membudidayakan terumbu karang, serta menyediakan pelatihan kepada masyarakat sehingga model transplantasi akan dihasilkan. Subjek dari pelatihan ini adalah komunitas nelayan di Kecamatan Pananjung. Pelatihan disampaikan dalam tahapan: 1) identifikasi kondisi terumbu karang di Perairan Cagar Alam; 2) analisis kesiapan dan kemampuan masyarakat dalam mengembangkan budidaya terumbu karang, dan 3) pelatihan dalam budidaya terumbu karang bagi masyarakat. Sasaran dari kegiatan ini adalah untuk meningkatkan kualitas lingkungan perairan dan meningkatkan pengetahuan masyarakat setempat melalui pelatihan dalam budidaya terumbu karang. Ketika transplantasi siap, masyarakat setempat akan dapat mengembangkan usaha pariwisata mandiri, berdasarkan konservasi dan meningkatkan ekonomi masyarakat, sehingga membantu pemerintah dalam mewujudkan wisata bahari yang berkelanjutan.Kata Kunci: Ekowisata, Transplantasi Terumbu Karang, Wisata Bahari. ABSTRACTSince 1990 Pangandaran has developed into one of the main tourism destination in West Java which focuses its development on Marine Ecotourism. The development drawn high number of tourists and impacted the condition of the marine ecosystems. The coral reefs were slowly being damaged by tourists activities, plastics waste and pollution, thus the clarity of the water was degraded.This Program was conducted to analyze the level of damage to coral reefs and community preparedness in cultivating coral reefs, as well as providing training to the community so that the model of transplantion would be generated. The subjects of this training were fishermen communities in Pananjung Subdistrict. The training was delivered in the stages of: 1) identification of the condition of coral reefs in the Nature Reserve Waters; 2) analysis of community readiness and ability in developing coral reef cultivation, and 3) training in coral reef cultivation for the community. The target of this activity is to improve the quality of the aquatic environment and increase the knowledge of local communities through training in coral reef cultivation. Whenever the transplantation is ready, the local community will be able to develop an independent tourism business, based on water conservation, and improve the economy of the community, thus helping the government in realizing a sustainable marine tourism.Keywords: Coral Reef Transplantation, Ecotourism, Marine tourism.